War and Peace in the Western Political Imagination : From Classical Antiquity to the Age of Reason - Manning, Roger B. (London Bloomsbury Academic)
The study of war in all periods of prehistory and recorded history has always commanded the attention of historians, dramatists, poets and artists. The study of peace has, however, not yet gained a comparable readership, and the subject is attracting an increasing amount of scholarly research. This volume presents the first work of academic research to tackle this imbalance head on. It looks at war and peace through the ages, from the Classical world through to the 18th century. It considers the nature and advocacy of war and peace both from an historical perspective but also a philosophical one, particularly looking at how universal peace, which began as a personal philosophy, became over the centuries a political philosophy that underpins much of modern society$1 (Bs attitudes towards warfare and militarism.s
English
Keywords: Military history; History; Military History; War and Peace; Classical History; 18th Century History; Political Philosophy